Use of Epivolve phage display to generate a monoclonal antibody with opsonic activity directed against a subdominant epitope on extracellular loop 4 of Treponema pallidum BamA (TP0326) - Ferguson, Mary R.; Delgado, Kristina N.; McBride, Shannon; Orbe, Isabel C.; La Vake, Carson J.; Caimano, Melissa J.; Mendez, Qiana; Moraes, Trevor F.; Schryvers, Anthony B.; Moody, M. Anthony; Radolf, Justin D.; Weiner, Michael P.; et al. (Frontiers in Immunology, 2023)
Syphilis, a sexually transmitted infection caused by the spirochete Treponema pallidum (Tp), is resurging globally. Opsonic antibodies (Abs) targeting surface-exposed epitopes of the spirochete's outer membrane proteins (OMPs) are believed to promote macrophage-mediated clearance of the bacterium during infection and are presumed to be key to vaccine development.Tp's repertoire of outer membrane proteins includes BamA (β-barrel assembly machinery subunit A/TP0326), the central component of the molecular machine that inserts newly exported OMP precursors into the OM lipid bilayer. BamA is a bipartite protein consisting of an 18-stranded βbarrel with nine extracellular loops (ECLs) and five periplasmic POTRA (polypeptide transportassociated) domains. Antisera directed against BamA ECL4 promote internalization of Tp by rabbit peritoneal macrophages. Herein, we employed a novel two-stage, phage display strategy, termed "Epivolve" (for epitope evolution), to generate five site-directed murine monoclonal Abs (mAbs) targeting a centrally located peptide (S2) of BamA ECL4. Each of the five mAbs demonstrated reactivity by immunoblotting and ELISA to nanogram amounts of BamA ECL4 displayed by a Pyrococcus furiosus thioredoxin (PfTrx) scaffold (PfTrx BamA/ECL4 ). One mAb containing a unique amino acid sequence in both light and heavy chains showed activity in an opsonophagocytosis assay employing murine bone marrow-derived macrophages. Mice and rabbits hyperimmunized with PfTrx BamA/ECL4 produced opsonic antisera that strongly recognized the ECL presented in a heterologous scaffold and overlapping ECL4 peptides including S2. In contrast, Abs generated during Tp infection of mice and rabbits poorly recognized the peptides, indicating that S2 contains a subdominant epitope. Epivolve, which circumvents the natural immune response, can be utilized for the generation of mAbs that target subdominant opsonic epitopes in ECLs of Tp OMPs.